Revisiting tools in numeracy learning: the role of authentic digital tools - Sakurai, Justine; Goos, Merrilyn (Frontiers in Education, 2023)
This conceptual analysis paper argues for an expansion to the definition of tools in Goos et al. (2012) model of numeracy. As the digitalisation of society progresses at an ever-quickening pace, mathematical processes that were once considered only necessary for higher level occupations and tasks are now everyday requirements for successful participation in modern life and workplaces. Mathematical acts are routinely undertaken on a normal day because of the technology we use in daily life. For example, the act of driving a car has a mathematical basis; the driver has awareness of the location of the destination, reads multiple instruments and indicators including speed and fuel consumption, and interprets digital maps or navigation aids.Authentic digital tools and devices that are used in the real world that undertake mathematical processes can change the mathematics that is to be done. Rapid developments in mathematical technology, alongside the ubiquity of digital devices, the broad scope of functions and ease of use, has advanced the mathematical processes that digital tools can perform. The specificity and functionality of current digital tools can influence both the approach to and the application of the mathematics.To keep pace with society trends and demands, the tools used in the teaching and learning of numeracy should reflect the level of mathematical knowledge and skills required for successful participation in 21 st Century life. Given that the digitalisation of tools means they are no longer bound by time and space, they can be shared instantaneously. This agile ease of use suggests these tools may be suitable for use in the classroom. It is important therefore that educators find pedagogical ways to use real-world digital tools in authentic ways.This paper explores the current definition of numeracy tools found in literature and curricula and considers an expansion to the definition to fit with current technological directions. A model for implementation will be considered, and a suggested evaluation of the expanded model as a vehicle for learning numeracy is proposed.